2020
DOI: 10.1016/j.envint.2019.105366
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emission factors of mineral fertilisers in the UK and Ireland: A Bayesian analysis of 20 years of experimental data

Abstract: Highlights We compiled datasets of N 2 O emission factors (EFs) from 21 separate studies. A Bayesian approach improves uncertainty analysis of EFs. AN applications were lower for applications to arable fields than to grasslands. Microbial inhibitors reduce emissions of N 2 O from mineral fertilisers significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 60 publications
3
15
0
Order By: Relevance
“…All three oil palm/riparian forest transects were within one km 2 of each other and received the same management; yet, we saw differences in N 2 O fluxes across the three transects. This highlights the inherent high spatial variability of soil N 2 O fluxes, as described many times in the literature (Davidson et al, 2000;Reay et al, 2012;Cowan et al, 2015Cowan et al, , 2020Drewer et al, 2021). The complexity of these two investigated ecosystems, oil palm plantations (OP) and riparian forests (RR) is very high, demonstrated by very high variability within sites as well as between sites.…”
Section: Discussionsupporting
confidence: 54%
“…All three oil palm/riparian forest transects were within one km 2 of each other and received the same management; yet, we saw differences in N 2 O fluxes across the three transects. This highlights the inherent high spatial variability of soil N 2 O fluxes, as described many times in the literature (Davidson et al, 2000;Reay et al, 2012;Cowan et al, 2015Cowan et al, , 2020Drewer et al, 2021). The complexity of these two investigated ecosystems, oil palm plantations (OP) and riparian forests (RR) is very high, demonstrated by very high variability within sites as well as between sites.…”
Section: Discussionsupporting
confidence: 54%
“…One way to reduce uncertainty when calculating cumulative emissions is to apply a Bayesian interpolation approach (Levy et al 2017;Cowan et al 2019Cowan et al , 2020. In this method, daily fluxes are interpolated by fitting values to a spatial log-normal distribution over time, i.e.…”
Section: Re-assessment Of the Tier 1 Efs For Irish Agricultural Systemsmentioning
confidence: 99%
“…Cowan et al [13] reviewed a dataset of N 2 O-EFs from 21 separate studies carried out on arable land and managed grasslands across the UK and Ireland over the past 20 years. This study showed that ammonium nitrate (AN) and CAN, which both contain NO 3 − -N and NH 4 + -N in a 50:50 ratio on an N basis, were the largest N 2 O emitter of the fertilizer types examined.…”
Section: Introductionmentioning
confidence: 99%